Pengaruh Organizational Trust, Empowering Leadership, Psychological Safety Dan Group Conflict - Ade Nur Sitta Dewi; Lia Amalia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In a knowledge-based economy, employees' perceptions of psychological safety in their work units are critical to group conflict This study aims to test and analyze how the influence of organization trust, epowering leadership, psychological safety and group conflict as mediating variables in retail companies in Jakarta The population in this study is employees or employees in retail companies consisting of staff consignment levels, as many as 150 respondents who come from employees or employees of permanent worker status and employees or employees of contract status with a service period of more than one year. Measurement techniques that use data collection tools in the form of questionnaires with online dissemination methods. Data analysis method using SEM (Structural Equitation Model). which is operated through the Smarts (Partial Least Square) program. The results showed that the variable of organization trust in psychological safety through group conflict showed that the value wssas positive. situations where psychological safety is well created in the workplace. Team members feel comfortable talking openly about the issues they're facing and asking questions when they need help. Leaders tend to create strong relationships with their team members, getting to know them as individuals, especially their work style, preferred working hours, strengths, areas of development and important commitments outside of work.